ZnO thin films containing aliovalent ions for NO2 gas sensor activated by visible light. Issue 17 (1st September 2021) - Paolucci, V.; De Santis, J.; Lozzi, L.; Rigon, M.; Martucci, A.; Cantalini, C.
Abstract: In this paper we report on the combined visible-light (red λ = 630 nm; green λ = 570 nm; purple-blue λ = 430 nm) and mild thermal-activation modes (25 °C–100 °C) towards ppb-level NO2 detection of ZnO nanocrystalline film containing trivalent (Al-Ga) and tetravalent (Si-Ge) ions. Both trivalent and tetravalent doping trigger visible light fast response/recovery behavior as respect to dark conditions. Remarkably Purple-blue light (λ = 430 nm) combined with thermal activation at 75 °C OT results in best performances in terms of variation of sensor resistance as compared to that in dry air, topping maximum gas relative response RR= RGas /RAir  ≈ 20 for the 5% Si doped ZnO at 400 ppb NO2 . Aliovalent doping of ZnO is obtained using a colloidal heat-up synthesis yielding highly transparent in the visible range degenerately doped n -type ZnO semiconductors films which were characterized by SEM, XRD, XPS techniques to assess morphology, crystal phases and concentration of surface oxygen vacancies, respectively. Optical characterization of the doped films showed a distinctive localized surface plasmon resonance (LSPR) peak in the near infrared region, deriving from the free charge carrier. Aluminum doping is the most effective to narrow the band gap of the doped ZnO films down to 3.22 eV. The influence of the relative humidity (RH) on the gas sensing performances is investigated and for 40% RH a slight decrease of the NO2 relative response was observed. A consistent model explaining the gas sensing mechanism under dark and light conditions and the influence of RH is presented.